2020
DOI: 10.3390/medicina56050227
|View full text |Cite
|
Sign up to set email alerts
|

Stroke, Dementia, and Atrial Fibrillation: From Pathophysiologic Association to Pharmacological Implications

Abstract: The impact of stroke and dementia on disability and death is a major contemporary health issue [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…According to current guidelines [86] anticoagulation is recommended in AF patients with CHA2DS2-VASc score of 2 or more (3 or more in women) and should be considered in those with CHA2DS2-VASc score of 1 or more (2ormoreinwomen). Since hospitalized COVID-19 patients are usually older than 65 years and present in approximately 70% of cases with two or more comorbidities, most of AF patients require long-term anticoagulation [87] . Hemodynamically stable, hospitalized COVID-19 patients with AF may be treated with either unfractionated heparin, low molecular weight heparin (LMWH) or direct oral anticoagulants (DOACs), depending on the possibility of oral treatment, renal function and other clinical conditions.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…According to current guidelines [86] anticoagulation is recommended in AF patients with CHA2DS2-VASc score of 2 or more (3 or more in women) and should be considered in those with CHA2DS2-VASc score of 1 or more (2ormoreinwomen). Since hospitalized COVID-19 patients are usually older than 65 years and present in approximately 70% of cases with two or more comorbidities, most of AF patients require long-term anticoagulation [87] . Hemodynamically stable, hospitalized COVID-19 patients with AF may be treated with either unfractionated heparin, low molecular weight heparin (LMWH) or direct oral anticoagulants (DOACs), depending on the possibility of oral treatment, renal function and other clinical conditions.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…According to a recent survey of electrophysiology professionals, atrial fibrillation (AF) was the most commonly encountered cardiac arrhythmia observed in patients with COVID-19 infection [13] . Several mechanisms could be involved in the pathogenesis of AF in these patients; virus-induced cardiac injury that could lead to perimyocarditis, hypoxemia frequently occurring in these patients, systemic infection, common occurrence of the COVID-19 infection in older patients who are already susceptible to AF, and sympathetic nervous system overactivity could all account for such a high incidence of this arrhythmia in this particular population [ 13 , 21 ].…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…The pharmacological treatments currently administered in patients with COVID‐19 include antiviral agents, as Lopinavir/Ritonavir (LPN/RTN), and drugs with immune‐modulatory and/or anti‐inflammatory properties, as hydroxychloroquine (HQ) and azithromycin (AZT), which are currently off-label used in Chinese and Italian centers ( Dong et al, 2020 ; Russo et al, 2020a ). LPN/RTN causes the dose-dependent block of both human ether-a-go-go-related gene (HERG) potassium channels and delayed rectifier potassium current (IKr) channels predisposing to QT prolongation and torsade de pointes (TdP) ( Anson et al, 2005 ; Russo et al, 2020b ). Increased corrected QTc interval (QTc) has been reported in hospitalized COVID-19 patients treated with HQ/AZT ( Bun et al, 2020 ; Chorin et al, 2020 ; Cipriani et al, 2020 ; Hor et al, 2020 ; Mercuro et al, 2020 ; Ramireddy et al, 2020 ) alone or in combination, due the inhibitory effects on IKr channels.…”
Section: Introductionmentioning
confidence: 99%